Kepentingan Inggris dalam Memerangi Illegal Logging melalui Program Multistakeholder Forestry Programme di Indonesia - Salsabilla Amanda Putri; Hermini Susiatiningsih; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
UK is one of the countries that requires wood for the purpose of using both for structural and non-structural buildings. The high demand for wood has forced UK to ask Indonesia to continue to supply its wood needs. However, illegal logging has become a problem for the forestry sector in Indonesia which has caused many losses, ranging from the unstable timber market industry, the deteriorating economy, and the increasingly unsustainable state of the forest. This made the UK formulate a foreign policy for Indonesia by creating a cooperation scheme through the Multistakeholder Forestry Program. Based on this, the author aims to explain the UK's interest in establishing cooperation with Indonesia through the Multistakeholder Forestry Program in combating Illegal Logging. This paper will focus to explain and analyze the cooperation formed between UK and Indonesia in minimizing the illegal timber trade. This study uses qualitative methods with data collection through secondary sources. This study uses the theory of Neoclassical Realism by looking at the internal and external factors of the UK. The results of this study indicate that the cooperation between the UK and Indonesia has been able to improve forest governance in Indonesia and the UK can easily obtain legal and safe timber.Keywords: Illegal Logging, Cooperation, MFP, Indonesia, UK.